Citizenship and residence sales : rethinking the boundaries of belonging / edited by Dimitry Kochenov, Kristin Surak. - Kochenov, Dimitry, 1979-; Surak, Kristin, 1976- (Cambridge University Press, 2023)
Citizenship and residence by investment is a fast-growing global phenomenon. As of 2022, more than a third of all countries in the world offered paths to membership in exchange for a donation or investment into their economies. Yet we know little about how these programmes operate and debates in academia and the wider public are often misinformed by sensationalist cases. This book offers a multidisciplinary exploration of both citizenship and residence by investment on a global scale. Bringing together the expertise of leading legal scholars, economists, sociologists, political scientists, and historians, it provides an informative and empirically grounded assessment of the origins, operation, key causes, and the legal bases of the investment migration programmes. By so doing, the volume demystifies citizenship and residence by investment and takes a critical postcolonial global perspective, addressing key issues in belonging, exclusion, and inequality that define the world today.